Clinical, cytogenetic and molecular analyses of a rare case with ring chromosome 15 and review of the literature - Hui-Yuan Shao; Hong-Ling Wang; Hong Wu; Xiao-Yan Liu; Zong-Yu Miao (Taiwanese Journal of Obstetrics & Gynecology, 2020)
Objective: Ring chromosome 15 [r (15)], accompanied by a series of clinical symptoms, is a rare genetic disease. The genotype and phenotypic diversity of patients with r (15) still needed further enrichment. In this study we present a rare case of mosaic ring chromosome 15 with facial anomalies and extremities slenderness. Case report: This case involves a 30-year-old woman, unpregnancy within 6 years. Clinical examination of the patient only revealed facial anomalies and extremities slenderness. The result of routine G-band karyotyping was 46,XX,r(15)(p12q26.3)[53]/46,XX,r(15;15)(p11.2q26.3;p11.2q11.2)[28]/45,XX, -15[10]/46,XX,r(15;15)(p11q26.3;p11q26.3)[4]. SNP array was employed to investigate the genome copy number variations (CNVs). The result revealed that there was a micro-duplication of 2.0 Mb at 15q26.3(arr[ph19]15q26.3 (100,400,214- 102,429,112)×3). The duplicated chromosomal section encompassed genes including CHSY1, ALDHIA3, LRRK1, and INS1. We further compared to the cytogenetic characteristics and clinical symptoms of the patient with those already reported by reviewing the literature. Conclusion: This report is especially helpful to supplement the phenotypic diversity of patients with r (15).